2010
DOI: 10.1177/1742715010379308
|View full text |Cite
|
Sign up to set email alerts
|

Leader toxicity: An empirical investigation of toxic behavior and rhetoric

Abstract: This paper provides empirical support for the behavioral and rhetorical constructs associated with toxic leadership in organizational contexts. Two exploratory studies were conducted that examined behavior and rhetoric of leaders through the lenses of abusive, bullying, destructive, toxic, and tyrannical leadership theories. In a qualitative study, participants expressed their direct experiences with leader toxicity. Eight behavioral dimensions emerged. Integrating those findings, a 51-item leader behavior ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
199
0
27

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(239 citation statements)
references
References 16 publications
13
199
0
27
Order By: Relevance
“…Management strategy based on humanistic core values, supported by Quality Management, has been pointed out as important for co-worker health (Wreder, 2008). To ensure that managers and supervisors engage in appropriate healthy management behaviours, organisational resources should be dedicated to adequately training and monitoring the performance of leaders (Pelletier, 2011). According to Goldgruber and Ahrens (2010), health-promotion interventions are possible in every organisation, but before starting a health-promotion programme it is necessary to analyse the organisation and especially its culture.…”
Section: Introductionmentioning
confidence: 99%
“…Management strategy based on humanistic core values, supported by Quality Management, has been pointed out as important for co-worker health (Wreder, 2008). To ensure that managers and supervisors engage in appropriate healthy management behaviours, organisational resources should be dedicated to adequately training and monitoring the performance of leaders (Pelletier, 2011). According to Goldgruber and Ahrens (2010), health-promotion interventions are possible in every organisation, but before starting a health-promotion programme it is necessary to analyse the organisation and especially its culture.…”
Section: Introductionmentioning
confidence: 99%
“…589-590). Pelletier (2010) found that toxic leaders are also skilled at fostering an 'us/them' dichotomy for the purpose of enhancing cronyism ('us'); in promoting this dichotomy, leaders maliciously set constituents against one another by identifying scapegoats and inciting their followers to castigate them; toxic leaders erode unit cohesion and deflate esprit de corps; and that abusive leadership is related positively to turnover intentions and psychological distress, and related negatively to affective and continuance commitment, job and life satisfaction (p. 377). Elle (2012) found that toxic leadership styles undermine military values, erode trust, and create a negative organizational climate.…”
Section: Negative Impactsmentioning
confidence: 99%
“…about six months). Pelletier (2010) offered that bullying is using mental or physical strength against someone who is likely to be in a weaker or subordinate position to the person who is engaging in bullying.…”
Section: Abusive Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…So interpreted, it has only recently begun to attract scholarly attention from what, as yet, remains a very small group of researchers (e.g. Bolden et al, 2012;Evans et al, 2013;Juntrasook et al, 2013;Macfarlane, 2011Macfarlane, , 2012 Bedein, 2002;Bolden, 2007;Kellerman, 2004;Pelletier, 2010;Pullen & Rhodes, 2008] …”
Section: The Substance Of Research Leadershipmentioning
confidence: 99%